Mobility on slips. Or: How to invest in paper. The Aby Warburg style. (1st October 2017) - Krajewski, Markus
The article examines the relationship between Aby Warburg and his library by analysing the media which is involved: first, the arrangement of the books according to the library's principle of the 'law of thse good neighbour', which helps to order the books on the shelves. Second, the handling of the library is even more determined by Aby Warburg's use of index cards and card indexes. Like his card index which is situated between him and the library, Aby Warburg himself is in between two library paradigms: on the one hand, as a person of the nineteenth century, Warburg belongs to the supporters of the systematic shelving instead of cataloguing the book collection. On the other hand his work is based on swift associations and direct responses to research questions, the associations not only thought up by words, but also visually, manually to be re-arranged on the shelves, which turns out to be a rather clumsy practice. The motor and initiator of these new orders is the card index with its mobile elements, allowing quick connections between the entities and resulting in enormous processes of re-shuffling of whole shelves and systematic arrangements in the book collection. It is especially the combination of these usually incompatible paradigms that makes the Kulturwissenschaftliche Bibliothek Warburg such a unique institution and rich example of knowledge practices in the twentieth century.